Investigation on the optimum rehabilitation method in repairing road defect - Maizatul Nur Syafiqah, Mohd Idris (2019)
This paper describes the application of road maintenance management is crucial in order to maintain the road network for the safe and convenient movement of people and goods. An improperly maintenance of road can lead to the damage of the road structure. Other than that, road damage can represent an increasing of hazard to users that can contribute to road accidents and also increased the maintenance cost. This study is conducted to identify the current practice of road maintenance at Melaka; to identify the types of defects and common defects occurred and also the optimum rehabilitation method use to overcome the defects. Then, questionnaire was prepared based on literature review study, interview session and directed to 55 respondents involving with contractor and company that expert in new construction, pavement rehabilitation, pavement preservation and road maintenance. The survey was involving to give a scale (rank) from 1(very low importance), 2 (low importance), 3 (medium importance), 4 (high importance), and 5 (extremely high importance) to the expected optimum rehabilitation method. From the data analysis using relative importance index (RII) method, there are several types of defects that usually occur that may contribute to road accidents has been identified. Apart from these, this study also identified the optimum rehabilitation method to overcome the defects of the roads which could be practiced for better and more effective of maintenance management.